2014
DOI: 10.1098/rspa.2013.0453
|View full text |Cite
|
Sign up to set email alerts
|

Towards a complete model of soil liquefaction: the importance of fluid flow and grain motion

Abstract: When loosely packed water-saturated granular soils, for example sands, are subjected to strong earthquake shaking, they may liquefy, causing large deformations with great destructive power. The phenomenon is quite general and occurs in any fluid-saturated granular material and is a consequence of the transfer of stress from inter-grain contacts to water pressure. In modern geotechnical practice, soil liquefaction is commonly considered to be an ‘undrained’ phenomenon; pressure is thought to be generated becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…Changes in entropy due to heat generation are typically neglected for sands. Without the term for entropy, the simplified equation of [5] is equivalent to other consolidation equations used in geophysics (e.g. [4,22]).…”
Section: Consolidation Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in entropy due to heat generation are typically neglected for sands. Without the term for entropy, the simplified equation of [5] is equivalent to other consolidation equations used in geophysics (e.g. [4,22]).…”
Section: Consolidation Equationmentioning
confidence: 99%
“…Darcy's law is considered valid, at least in the case of earthquake-induced liquefaction [6]. Based on these assumptions, a complete model for liquefaction is given in [5]. After dropping terms that are related to the compressibility of the fluid, which is not expected to be of importance for homogeneous sand layers, a simplified equation is also proposed in [5].…”
Section: Consolidation Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sa'ari et al [7], the double-porosity soils have different hydraulic properties of two sub-region media due to different pore size characteristics. Existing research by Lakeland et al [8] had demonstrated that liquefaction is not a strictly undrained process via first principles analysis, but in fact observation of numerous earthquake events shows that the interplay between soil rearrangement, liquid migration, and permeability changes have led to loss of strength. The fracture porosity formation were characterized by water-bearing formations where groundwater flows along the fracture solid nd 2017, Surabaya -Indonesia rock, while a fracture is created as rock mass is broken down due to tectonic force [9].…”
Section: Introductionmentioning
confidence: 99%